2013
DOI: 10.1172/jci62980
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-mediated loss of ADAR1 in metastatic melanoma promotes tumor growth

Abstract: Some solid tumors have reduced posttranscriptional RNA editing by adenosine deaminase acting on RNA (ADAR) enzymes, but the functional significance of this alteration has been unclear. Here, we found the primary RNA-editing enzyme ADAR1 is frequently reduced in metastatic melanomas. In situ analysis of melanoma samples using progression tissue microarrays indicated a substantial downregulation of ADAR1 during the metastatic transition. Further, ADAR1 knockdown altered cell morphology, promoted in vitro prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
179
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(191 citation statements)
references
References 62 publications
8
179
0
Order By: Relevance
“…Recent studies reported that non-enzymatic ADAR1 participates in small RNA biogenesis in different organisms [19,20]. ADAR1 was suggested to interact with DICER to promote miRNA processing [22] or to form a complex with DGCR8 to inhibit pri-miRNA processing [21]. We found that ADAR1 binds directly to pri-miR302s, competes with DGCR8 and thus inhibits miRNA processing ( Figure 6).…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Recent studies reported that non-enzymatic ADAR1 participates in small RNA biogenesis in different organisms [19,20]. ADAR1 was suggested to interact with DICER to promote miRNA processing [22] or to form a complex with DGCR8 to inhibit pri-miRNA processing [21]. We found that ADAR1 binds directly to pri-miR302s, competes with DGCR8 and thus inhibits miRNA processing ( Figure 6).…”
Section: Discussionmentioning
confidence: 59%
“…It was recently reported that ADAR1 could either bind with DICER [22] or DGCR8 [21] to regulate miR-NA processing. Interestingly, we found that ADAR1 in hESCs was predominately localized to the nucleus (data not shown) as previously reported [49].…”
Section: Adar1 Acts As An Rna-binding Protein That Directly Inhibits mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to its previously mentioned editing function, ADAR1, can form a complex along with DGCR8, preventing the association between DGCR8 and Drosha during pri-miRNA processing. Moreover, it seems that ADAR1 can control the expression of more than 100 miRNAs which are positive regulators of metastatic programs in melanoma 91 ( Fig. 2A).…”
Section: Drosha Processing and Alterations In Cancermentioning
confidence: 99%